‘Political remittances’ - Tabar, Paul (2014)
This paper examines a particular event that occurred in Australia within the Australian-Lebanese community: it is the political mobilisation of a substantial number of this community to participate in the general elections that took place in Lebanon in June 2009. This event is analysed by looking into the various components of what we call ‘the Lebanese diasporic public sphere’. It is argued that this diasporic public sphere generates different political views and positions entertained by various members of the Australian-Lebanese community and materialised into specific ‘political remittances’ sent to Lebanon. Finally, an analysis of the impact of this political transfer to Lebanon is made in terms of a broader discussion of ‘political remittances’ as represented in the current literature.